Dymisje ministrów w lutym 1948 r. – jak było naprawdę? - Veber, Václav (Pamięć i Sprawiedliwość, 2012)
The dismissal of the non-communist politicians was the key event of the February 1948 political crisis in Czechoslovakia. The communists offi cially claimed that there were 12 dismissals even though on the critical day of 25 February 1948 President Beneš signed the total number of 14 dismissals. He could do something completely different in that situation to overcome the political crisis. His unconstitutional decision to support the Prime Minister and Communist Party of Czechoslovakia leader Klement Gottwald aided the communists’ smooth overtake of power, which was actually a coup. There are various speculations as to why he did that. It seems, however, that he was under pressure of Soviet secret agents, who threatened line with the expectations of the Soviet government and, fi rst and foremost, of Stalin himself.